Kebijakan Dividen Terhadap Harga Saham PT Unilever Indonesia Tbk Yang Terdaftar di Bursa Efek Indonesia - Dirgahayu Erri; Novita Andrianto Dwi (Universitas Bina Sarana Informatika, 2018)
Share prices describe the quality of a company. High stock prices indicate that companies perform well, and companies that perform well are companies that will be much in demand by investors, because investors expect high dividends that can improve the welfare of shareholders. The amount of dividends paid to shareholders depends on the dividend policy that has been taken by each company. The purpose of this study was to examine the effect of dividend policy on stock prices. Dividend policy is measured by the Dividend Per Share (DPS) indicator on the company's financial statements for the period 2012-2016. For stock prices are measured using the average closing of the monthly stock price for each year. The data used in this study are secondary data obtained from the IDX website and the official website of the company PT Unilever Indonesia. Analysis of research results used is measuring the magnitude of correlation, determination and simple regression. The processing of this research uses the SPSS 22 software application. The results show that the correlation between Dividend Per Share (DPS) to the Closing Share Price is very strong, that is equal to 0.991 with a variable contribution of 98.2%. While the remaining 1.8% is influenced by other factors not examined in this study. Based on the t test obtained the significance value of 0.001 is smaller than 0.05, so it can be concluded that the Dividend Per Share (DPS) has a significant influence on the Closing Price.Keywords: Dividends per Share, Closing Prices